Wear behavior of As-deposited and oxidized ternary (Zr,Hf)N coatings - Atar, E; Kayali, ES; Cimenoglu, H (Springer, 2005)
In the present study, the tribological performance of ternary (Zr,Hf)N coatings, whose Hf content was varied between 0 and 21 wt pct, has been systematically examined in the as-deposited and oxidized conditions. Coatings were applied on AISI D2 tool steel plates by arc physical vapor deposition (PVD). Oxidation was conducted at 400 degrees C for times up to 12 hours in air. Wear tests revealed pronounced improvement in the wear resistance with increasing Hf content in the as-deposited coatings. Oxidation for 12 hours yielded more than a fourfold increase in wear resistance. The beneficial effect of Hf on wear resistance decreased upon oxidation.
Keywords: Physical Vapor-Deposition; Ti-Zr-N; Hard Coatings; Vacuum-Arc; Oxidation Behavior; Low-Temperature; Multicomponent; Films; Multilayer; Crn